La musique dodécaphonique et sérielle une nouvelle histoire - Jedrzejewski, Franck 1958- (Brepols, 2021)
At the beginning of the twentieth century, Arnold Schönberg proposed a new way of composing in his Five Pieces for Piano that proceeded from a ?series of 12 tones which have no relation to each other?. A twelve-tone composition by René Leibowitz that was popularized in France originated from the small town of Mödling - a suburb of Vienna where Schönberg lived, and the site of a musical revolution. Composers who used this technique appropriates the series and adapted the principles of composition to suit their own sensibilities. While some divided the series into (more or less) autonomous fragments, others extended the series to include all musical parameters; still others constructed series of more than twelve tones or invoked matrix-based calculus. This book chronicles a technical history of serialism and highlights narratives that have not yet appeared in published literature by examining theoretical texts in numerous languages, some by composers whose works are translated here for the first time. This book constitutes the first major synthesis of the history of serialism published in French.
Keywords: Geschichte; Zwölftontechnik; Serielle Musik